Electrochemical performance of supercapacitor with glass wool separator under TEABF4 electrolyte - Mohd Ferdaus Mohammad Yaacob; Zulkarnain Ahmad Noorden; Muhammad Nizam Abdul Razak; Zuraimy Adzis; Jasrul Jamani Jamian (Bulletin of Electrical Engineering and Informatics, 2020)
The paper presents the electrochemical performance of supercapacitor with glass wool separator under organic electrolyte of tetraethylammonium tetrafluoroborate (TEABF4). The performance was evaluated using symmetrical two-electrode system and compared to an identical supercapacitor with commercially available cellulose paper separator under 1 M TEABF4. The application of glass wool separator reduces the bulk resistance of supercapacitor by 19.6%, promotes more efficient ions transfer across active surface of electrode and significantly improves specific capacitance by 19.1% compared to cellulose paper. The application of higher concentration TEABF4 (1.5 M) even improves the overall performance of glass wool-based supercapacitor by 32.2% reduction of bulk resistance and 61.9% increment in specific capacitance compared to 1 M TEABF4. In addition, the energy and power densities are significantly improved by 64% and 165%, respectively for the one with 1.5 M TEABF4. In general, the low-cost material glass wool material has great potential to replace commercially available cellulose paper as separator in developing much better supercapacitor.